THE EFFECT OF PROFITABILITY, CASH HOLDINGS, SALES GROWTH, INSTITUTIONAL OWNERSHIP STRUCTURE AND CORPORATE TAX RATE ON CAPITAL STRUCTURE - Bambang Sugiharto; Trisandi Eka Putri; Qiara Luthfiani (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
The study aims to determine the effect of profitability, cash holdings, sales growth, institutional ownership structure, and corporate tax rate on the capital structure of a case study of Basic and Chemical Industry Sector Companies listed on the Indonesia Stock Exchange for 2017-2020. In this study, using a purposive sampling method, and samples that fit the criteria 221 data were obtained on Basic and Chemical Industry Sector Companies listed on the Indonesia Stock Exchange for 2017-2020. And the data were analyzed using IBM SPSS Statistics 22 program. Partial result (t-test), profitability and cash holdings have a negative significant effect on capital structure, sales growth has a positive significant effect on capital structure. Meanwhile, institutional ownership structure and corporate tax rate have no significant effect on capital structure. The simultaneous test result (F test) shows that the profitability, cash holdings, sales growth, institutional ownership structure, and corporate tax rate simultaneously affect capital structure